2015
DOI: 10.1091/mbc.e14-11-1510
|View full text |Cite
|
Sign up to set email alerts
|

Pan1 regulates transitions between stages of clathrin-mediated endocytosis

Abstract: The Saccharomyces cerevisiae endocytic protein Pan1 is critical for coat interactions during three transitions of the endocytic pathway. Pan1 depletion arrests endocytosis and causes actin misregulation, leading to actin flares that are connected to the coat but not the membrane. The Pan1 central region is critical for endocytic and essential functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 46 publications
2
29
2
Order By: Relevance
“…Ten of the 33 genes identified in this screen encode proteins involved in vesicle transport or cytoskeleton function (Table 1; Figure 2) [14, 15, 16, 17, 18, 19, 20, 21, 22, 23]. Close homologs of nine are highly expressed in root hairs, and three of these are required for root hair growth in A. thaliana .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten of the 33 genes identified in this screen encode proteins involved in vesicle transport or cytoskeleton function (Table 1; Figure 2) [14, 15, 16, 17, 18, 19, 20, 21, 22, 23]. Close homologs of nine are highly expressed in root hairs, and three of these are required for root hair growth in A. thaliana .…”
Section: Resultsmentioning
confidence: 99%
“…Mp SRI2 (Mp SHORT RHIZOIDS2 ) encodes an EF-hand-containing protein that is similar to S. cerevisiae PAN1. PAN1 is required for association of the ARP-actin polymerization complex with clathrin-coated vesicles during endocytosis in yeast [19]. Mp SHORT RHIZOIDS1 (Mp SRI1 ) encodes a protein similar to S. cerevisiae RIC1, which is a guanine exchange factor involved in activating Ypt6p GTPase and required for trafficking from early endosomes to the Golgi late in the endocytosis pathway [23].…”
Section: Resultsmentioning
confidence: 99%
“…A pan1-null strain is inviable, but with the use of the auxin-inducible degron system, which acutely depletes proteins through proteasome-mediated degradation (Eng et al, 2014;Nishimura et al, 2009), Pan1 has been found to be required for the transition between early CME events and actin assembly (Bradford et al, 2015). Interestingly, when Pan1 and its interaction partner End3 are simultaneously depleted, the 'early module' and 'early-mid coat module' proteins are capable of colocalizing at the cell cortex; however, the WASp and myosin, scission and actin modules remain spatiotemporally uncoupled from these coat proteins (Sun et al, 2015).…”
Section: Tying Everything Togethermentioning
confidence: 99%
“…We deleted C-terminal, 430 amino-acid long, unstructured part of Pan1 (Pan1(1-1050)); and C-terminal, supposedly ∼7 nm long, THATCH domain of Sla2 (Brett et al, 2006). Both deletions were previously shown to retain essential functions, proper localization and expression levels of respective wild-type proteins (Wesp et al, 1997;Skruzny et al, 2012;Bradford et al, 2015). Contrary to full-length Pan1 and Sla2, we detected FRET of Pan1(1-1050) with Clc1 and Chc1 (1.4% and 1.2%; p=0.004 and p=0.001 against Pan1-Clc1 and Pan1-Chc1 pairs, respectively; n=12 cells), and between Sla2dTHATCH and Clc1 (1.4%; p=0.009 against Sla2-Clc1; n=14 cells) ( Figure 3B).…”
Section: Endocytic Coat Proteins Localize On Both Sites Of the Clathrmentioning
confidence: 99%
“…Finally, we tested the proposed Pan1 orientation by using a functional Pan1(402-1480) truncation, which N-terminally shortened Pan1 after its first EH domain (Bradford et al, 2015). We compared FRET values of this N-terminal truncation and the Pan1 N-terminus towards both clathrin subunits.…”
Section: Key Coat Proteins Transverse the Clathrin Lattice In The Memmentioning
confidence: 99%